American sugar kingdom : the plantation economy of the Spanish Caribbean, 1898-1934 - Ayala, César J. (University of North Carolina Press, 1999)
"Examines patterns of investment and principal groups of investors, interactions between U.S. capitalists and native planters, contrasts between new and old regions of sugar monoculture, the historical formation of the working class on sugar plantations, and patterns of labor migration."--Page 4 of cover